Acceleration of Body Clearance of DiethylCarbamazine By Oral Activated Charcoal - Orisakwe, Orish E.; Ilondu, Ndidi A.; Afonne, O.Johnson; Ofoefule, Sabinus I.; Orish, Chinna N. (Pharmacological research, 2000)
The effect of activated charcoal (AC) on body clearance of diethylcarbamazine (DEC) was investigated in six healthy volunteers. On three occasions at weekly intervals, each subject received 150 mg of DEC with 350 ml of water. One and two weeks later, 150 mg of DEC plus 7.5 g and 15 g of AC, respectively, in 350 ml of water as a charcoal slurry. The non-renal clearance of DEC expressed as the total body clearance of DEC was increased after treatment with AC. The 45.2, 79.6 percent and 58.6, 81.6 percent reductions in maximum concentration and area under the concentration–time curve, respectively, suggest an appreciable adsorption of DEC by AC (7.5 and 15 g) in the gut. Serum eliminating half-life was decreased upon treatment with AC (7.5 and 15 g). These results indicate that AC accelerates the body clearance of DEC by increasing non-renal elimination of the drug.